2014
DOI: 10.5719/hgeo.2014.81.27
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder perspectives on climate change effects on tourism activities in the northern Romanian Carpathians: Vatra Dornei resort case study

Abstract: Abstract:Less approached by scientific literature, stakeholder perspective on the effects of climate change for tourism activities is a very actual topic. As an essential part of the complex study of climate -tourism relationship, it needs to be investigated and illustrated through study cases. The present paper approaches this original topic for Vatra Dornei complex spa and mountain resort. Located in the northern part of Romanian Carpathians this destination depends to a great extent on climate resources whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Although the term climate change is still a novel concept for many respondents in this study, and was generally related to current climate variability and environmental changes in the region, the findings from this study suggested that there was a strong awareness and acceptance of the reality of climate change among local destination stakeholders. This finding was consistent with the conclusions from the wider literature on public perceptions of climate change (Becken et al, 2014;Dunlap, 1998;Leiserowitz, 2005;Lorenzoni & Pidgeon, 2006), as well as the literature on tourism and climate change that assessed the perspectives of tourism destination stakeholders in developed countries on climate change (Jenkins & Nicholls, 2010;Ruhanen & Shakeela, 2012;Saarinen & Tervo, 2006;Tervo-Kankare, 2011;Trawöger, 2014), and developing ones (Anup, Parajuli, & Bahadur, 2014;Belle & Bramwell, 2005;Dincǎ et al, 2014).…”
Section: Addressing Research Objective Onesupporting
confidence: 86%
See 1 more Smart Citation
“…Although the term climate change is still a novel concept for many respondents in this study, and was generally related to current climate variability and environmental changes in the region, the findings from this study suggested that there was a strong awareness and acceptance of the reality of climate change among local destination stakeholders. This finding was consistent with the conclusions from the wider literature on public perceptions of climate change (Becken et al, 2014;Dunlap, 1998;Leiserowitz, 2005;Lorenzoni & Pidgeon, 2006), as well as the literature on tourism and climate change that assessed the perspectives of tourism destination stakeholders in developed countries on climate change (Jenkins & Nicholls, 2010;Ruhanen & Shakeela, 2012;Saarinen & Tervo, 2006;Tervo-Kankare, 2011;Trawöger, 2014), and developing ones (Anup, Parajuli, & Bahadur, 2014;Belle & Bramwell, 2005;Dincǎ et al, 2014).…”
Section: Addressing Research Objective Onesupporting
confidence: 86%
“…Climate change has also affected a number of winter tourism sites in developing countries such as China, Nepal and Tibet due to decreased snow cover and increased landslides associated with prolonged and intense rainfall (Fort, 2014;Ren, 1996;Yan et al, 2014). However, Scott et al (2007) noted that the impacts of a changing climate on the ski industry are felt unevenly in the skiing sector as some resorts cease to operate and demand is shifted to those that are more climate-resilient (Dincǎ, Surugiu, Surugiu, & Frenţ, 2014).…”
Section: More Frequent and Larger Forest Firesmentioning
confidence: 99%
“…Climate change is having significant impacts on many facets of everyday life, and the commercial recreation and tourism fields are often at the forefront of these impacts as consumers are faced with making difficult decisions with discretionary income (Ana Irina, Camelia, Marius, Cristi, 2014). Understanding how these impacts are changing the way people engage in recreation and tourism activities is essential to maintaining successful businesses and providing satisfying opportunities for consumers.…”
Section: Introductionmentioning
confidence: 99%
“…Understanding local climate conditions is also important in various phases of tourism development: planning the hotel location, an organization of events, development of infrastructure, but also for maintaining the sustainable number of tourist in various part of the year. Many papers indicate that climatic characteristics of destinations, but also climate change can have a major influence on tourist flows (Gössling, et al, 2006;Hein, et al, 2009;Giannakopoulos, et al, 2011;Dinca, et al, 2014;León, Araña, 2016). Accord-ing to IPCC (Intergovernmental Panel on Climate Change, 2013) and its AR5 (Fifth Assessment Report), global surface temperature change for the end of the 21st century is likely to exceed 1.5°C for all scenarios.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Dinca et al (2014) studied the stakeholder perspective on the effects of climate change for tourism activities in Vatra Dornei complex (spa and mountain resort in the northern part of Romanian Carpathians). In this paper, the authors also emphasize that this destination depends on to a great extent on climate resources which show a clear variability of main parameters on which its outdoor activities are based.…”
Section: Introductionmentioning
confidence: 99%